β-Nicotinamide Mononucleotide (NMN) Administrated by Intraperitoneal Injection Mediates Protection Against UVB-Induced Skin Damage in Mice - Zhou X; Du HH; Long X; Pan Y; Hu J; Yu J; Zhao X (Dove Medical Press, 2021)
Xianrong Zhou,1- 4,* Hang-Hang Du,5,* Xingyao Long,1- 3 Yanni Pan,1- 3 Jian Hu,6 Jianjun Yu,6 Xin Zhao1- 3 1Chongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Chongqing, People's Republic of China; 2Chongqing Engineering Research Center of Functional Food, Chongqing University of Education, Chongqing, People's Republic of China; 3Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, People's Republic of China; 4Department of Food and Nutrition, College of Medical and Life Sciences, Silla University, Busan, South Korea; 5Department of Plastic Surgery, Chongqing Huamei Plastic Surgery Hospital, Chongqing, People's Republic of China; 6R&D Department, Effepharm (Shanghai) Co., Ltd, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin ZhaoChongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Xuefu Main Street 9, Chongqing, 400067, People's Republic of ChinaEmail zhaoxin@cque.edu.cnJianjun YuR&D Department, Effepharm (Shanghai) Co., Ltd, Room 201, Building 12, No. 1, Wangdong Middle Road, Sijing Town, Shanghai, 201601, People's Republic of ChinaEmail jianjun.yu@effepharm.comObjective: Ultraviolet light is an important environmental factor that induces skin oxidation, inflammation, and other diseases. Nicotinamide mononucleotide (NMN) has the effect of anti-oxidation and improving various physiological processes. This study explores the protective effect of NMN monomers given via intraperitoneal injection on UVB-induced photodamage.Methods: We used a murine model of UVB-induced photodamage to evaluate the effect of an NMN monomer on photoaging skin by assessing skin and liver tissue sections, serum and skin oxidative stress levels, inflammatory markers, mRNA expression, and protein expression of skin- and liver-related genes.Results: The results showed that NMN treatment blocked UVB-induced photodamage in mice, maintaining normal structure and amount of collagen fibers, normal thickness of epidermis and dermis, reducing the production of mast cells, and maintaining complete organized skin structure. NMN intraperitoneal injection also maintained the normal morphology of the mouse liver after UVB exposure. Meanwhile, NMN intraperitoneal injection was found to increase antioxidant ability and regulate the proinflammatory response of the skin and liver to UVB irradiation by enhancing the activity of antioxidant enzymes, release of anti-inflammatory cytokines, reduction of hydrogen peroxide production (H2O2), and decreased inflammatory cytokines. Furthermore, RT-qPCR results indicated that NMN reduced oxidative stress of skin and liver by promoting the activation of the AMP-activated protein kinase (AMPK) signaling pathway and further increasing the expression of downstream antioxidant genes of AMPK. RT-qPCR results also revealed that NMN treatment could downregulate the mRNA expression of interleukin (IL)-6, interleukin (IL)-1β, and tumor necrosis factor (TNF)-α, and upregulate NF-kappa-B inhibitor-α (IκB-α) and interleukin (IL)-10 by inhibiting the activation of nuclear factor-κBp65 (NFκB-p65). Finally, NMN upregulated AMPK, IκB-α, SOD1, and CAT in the skin and downregulated NF-κBp65 protein expression, which is in line with the RT-qPCR results.Conclusion: Based on the above results, NMN monomer treatment with intraperitoneal injection also block the photodamage caused by UVB irradiation in mice by regulating the oxidative stress response and inflammatory response.Keywords: nicotinamide mononucleotide, UVB, antioxidant, NF-κBp65 signaling pathway, AMP-activated protein kinase signaling pathway